Chitosan as a biopesticide against rice (Oryza sativa) fungal pathogens, Pyricularia oryzae and Rhizoctonia solani - Wong, Mui Yun; Surendran, Arthy; Burhanudin, Farhana; Saad, Nur Madhihah (Universiti Putra Malaysia Press, 2020)
The antifungal potential of chitosan obtained from shellfish was studied in both in vitro and in vivo conditions against Pyricularia oryzae and Rhizoctonia solani, causal agents of the blast and sheath blight diseases in rice, respectively. A total of 100% inhibition of mycelial growth was observed on both P. oryzae and R. solani when a 4% concentration of chitosan was used in this study. A significant reduction in both disease incidence and disease severity was observed between the treated and untreated rice plants. The disease controlling efficacy of chitosan was concentration-dependent with a negative correlation. The disease reduction (DR) capacity of chitosan in this study ranged between 47-95%. Chitosan was able to reduce disease severity (DS) of blast by 85% and sheath blight by 95% while disease incidence (DI) of blast by 77% and sheath blight by 89%. The results demonstrated that chitosan extracted from shellfish has the potential to be developed as a biopesticide for sustainable control of both blast and sheath blight diseases in rice and has broad-spectrum capacity in controlling both diseases.